2014
DOI: 10.18632/oncotarget.2185
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase RBP2 induced by Helicobactor Pylori CagA participates in the malignant transformation of gastric epithelial cells

Abstract: Gastric epithelial cell malignant transformation induced by Helicobactor Pylori contributes to tumor development, but the underlying mechanisms for this remain unclear. Here we demonstrate that RBP2, a newly identified histone demethylase, can be induced by CagA via PI3K/AKT-Sp1 pathway depending on AKT phosphorylation. Sp1 directly binds to RBP2 promoter and enhances its expression then the upregulated RBP2 significantly increases Cyclin D1 transcription, which contributes to gastric epithelial cell malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…pylori also plays a role in immunomodulation by inhibiting both B‐cell and T‐cell lymphocyte proliferation that may induce a persistent inflammatory microenvironment . In addition to the induction of inflammatory cell infiltration, toxin produced by H. pylori affects the GES‐1 cells and can change the gene expression of the latter, damaging the integrity of gastric epithelial cells . Our data demonstrated that H. pylori infection significantly increased the expression of p42.3 gene in GES‐1 cells, which further emphasized the role of H. pylori as a class I carcinogen.…”
Section: Resultssupporting
confidence: 53%
“…pylori also plays a role in immunomodulation by inhibiting both B‐cell and T‐cell lymphocyte proliferation that may induce a persistent inflammatory microenvironment . In addition to the induction of inflammatory cell infiltration, toxin produced by H. pylori affects the GES‐1 cells and can change the gene expression of the latter, damaging the integrity of gastric epithelial cells . Our data demonstrated that H. pylori infection significantly increased the expression of p42.3 gene in GES‐1 cells, which further emphasized the role of H. pylori as a class I carcinogen.…”
Section: Resultssupporting
confidence: 53%
“…In contrast, overexpression of RBP2 favors anchorage‐independent growth. It is suggested here that RBP2 may promote senescence bypass by H3K4 demethylation at promoters of cell cycle inhibitors .…”
Section: The Rnai Machinery and Mirs In The Modulation Of Senescencementioning
confidence: 85%
“…The infection of gastric epithelial cells with H. pylori leads to hyperacetylation of histone H4 [82], which induces the binding of histone H1 to ATP [83] and causes histone H3 dephosphorylation and deacetylation [41, 84]. These changes result in the abnormal expression of oncogenes and tumor suppressor genes [85, 86], which contributes to malignant transformation of gastric epithelial cells.…”
Section: H Pylori Infection Promotes Gastric Cancer Mainly Through Ementioning
confidence: 99%